INTERACTIVE COMPUTER SIMULATION AS A RESPONSE TO CONTEMPORARY PROBLEMS OF TECHNICAL EDUCATION - Prauzner, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The theory of teaching, commonly referred to as didactics, is gaining increasing recognition in the work of a teacher immersed in the present-day reality of education. It appears right to assume that familiarity with the changing world should inspire innovativeness aimed to eliminate unnecessary or inadequate phenomena. For this reason, it is advisable to treat didactics as a theoretical discipline with practical implications for teachers, especially in the process of transforming and perfecting the educational system to make it meet the real social and economic challenges. The paper presents empirical studies conducted in the period 2010-2015 among full-time and weekend students of Safety Engineering at Jan Dlugosz University in Czestochowa, Poland. The studies were aimed to test the hypothesis that using deterministic computer simulations in the didactic process fosters learning effectiveness in the field of technological education as compared to traditional methods applied in a laboratory. The investigation employed extended methodology including verifying detailed hypotheses by means of empirical studies proved to be significant by the c2 (chi-squared) test. It was also situated within the general theory of education, additionally addressing the postulates of constructivist and cognitivist paradigms of learning.